Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = \(\dfrac{3}{3\times7}\)+ \(\dfrac{3}{7\times11}\)+ \(\dfrac{3}{11\times15}\)+...+\(\dfrac{3}{107\times111}\)
A = \(\dfrac{3}{4}\) \(\times\)( \(\dfrac{4}{3\times7}\)+ \(\dfrac{4}{7\times11}\)+ \(\dfrac{4}{11\times15}\)+...+\(\dfrac{4}{107\times111}\))
A = \(\dfrac{3}{4}\) \(\times\) ( \(\dfrac{1}{3}\) - \(\dfrac{1}{7}\) + \(\dfrac{1}{7}\) - \(\dfrac{1}{11}\)+ \(\dfrac{1}{11}\) - \(\dfrac{1}{15}\)+...+ \(\dfrac{1}{107}\)- \(\dfrac{1}{111}\))
A = \(\dfrac{3}{4}\) \(\times\) ( \(\dfrac{1}{3}\) - \(\dfrac{1}{111}\))
A = \(\dfrac{9}{37}\) > \(\dfrac{9}{45}\) = \(\dfrac{1}{5}\)
Vậy \(\dfrac{3}{3\times7}\) + \(\dfrac{3}{7\times11}\)+ \(\dfrac{3}{11\times15}\) + ...+ \(\dfrac{3}{107\times111}\) > \(\dfrac{1}{5}\) ( đpcm)
Bạn ơi thế này thì đúng hơn chứ:
\(\dfrac{3}{3.7}+\dfrac{3}{7.11}+\dfrac{3}{11.15}+...+\dfrac{3}{107.111}>\dfrac{1}{5}\)
a)\(VT=\frac{1}{2\cdot5}+\frac{1}{5\cdot8}+...+\frac{1}{\left(3n-1\right)\left(3n+2\right)}\)
\(=\frac{1}{3}\left[\frac{3}{2\cdot5}+\frac{3}{5\cdot8}+...+\frac{3}{\left(3n-1\right)\left(3n+2\right)}\right]\)
\(=\frac{1}{2}-\frac{1}{5}+\frac{1}{5}-\frac{1}{8}+...+\frac{1}{3n-1}-\frac{1}{3n+2}\)
\(=\frac{1}{2}-\frac{1}{3n+2}=\frac{3n+2}{2\cdot\left(3n+2\right)}-\frac{2}{2\cdot\left(3n+2\right)}\)
\(=\frac{3n+2-2}{6n+4}=\frac{3n}{6n+4}=VP\)
3 2 x + 1 x 11 = 2673
3 2 x + 1 = 2673 : 11
3 2 x + 1 = 243
3 2 x + 1 = 3 5
=> 2 x + 1 = 5
2 x = 4
x = 2
3^2x+1 =2673/11
3^2x+1 =243
x=2